Literature Review: Overview of Health Literacy in Society - Putri Ayuni Alayyannur; Rr. Sri Rejeki Eviyanti Puspita Sari; M. Malik Al Hakim (Tecno Scientifica Publishing, 2025)
Health literacy is one of the determinants of health that can help develop public health. It is an important component in empowering individuals regarding their health. Someone with low health literacy has limited information about their health condition and does not understand how to maintain it. The aim of this review was to explore health literacy in society and the factors that influence it. A literature search was conducted in March 2021. Research sources were taken from several databases, namely ScienceDirect, ProQuest, and PubMed. The ScienceDirect database contained 69,360 articles, ProQuest 130,006, and PubMed 17,038. From all databases, only 45 articles met the inclusion criteria. The variables in this study were the domains of health literacy and the factors that influence it. This literature review showed that the domains